Rheological and calorimetric properties of corn‐, wheat‐, and cassava‐ starches and soybean protein concentrate composites - Colombo, Andrés (2011)
The effect of soy protein concentrate (SPC) on the rheological and calorimetric properties of corn, wheat, and cassava starches was assessed. SPC increased To values and decreased the ΔH of all tested starches, which could be related to lower availability of water for starch gelatinization and/or to the interactions between SPC and amorphous regions of starch granules. SPC and sugar addition modified the viscosity parameters (obtained through a rapid visco-analyser) of starch pastes, which was attributed to an increase in solid content and to the interaction of proteins with the starch dispersed phase. Frequency sweeps were carried out with a rheometer on gels containing starch, SPC, and sucrose. SPC raised storage and loss modulus, producing more consistent starch gels. Besides, penetration tests showed that SPC steadily increased starch gel firmness. Scanning electron micrographs showed that protein concentrate produced gels with closer structures. Summarizing, the starch and SPC in the gels obtained were expected to be arranged in a two-phase system. Results showed that it is possible to achieve different textures for starch dessert formulations.